2013
DOI: 10.1088/0953-2048/26/7/075001
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in 122 antimonide SrPt2Sb2

Abstract: The crystal structure, superconducting properties, and electronic structure of a novel superconducting 122-type antimonide, BaPt 2 Sb 2 , have been investigated by measurements of powder X-ray diffraction patterns, electrical resistivity, ac magnetic susceptibility, specific heat as well as ab-initio calculations. This material crystallizes in a new-type of monoclinic variant of the CaBe 2 Ge 2 -type structure, in which Pt 2 Sb 2 layers consisting of PtSb 4 tetrahedra and Sb 2 Pt 2 layers consisting of SbPt 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 45 publications
6
30
0
Order By: Relevance
“…This is consistent with optical conductivity results in SrPt 2 As 2 [24] and the quasi-nesting features obtained by band structure calculations in SrPt 2 As 2 [26]. The negative curvature of the electrical resistivity temperature dependence (d 2 ρ/dT 2 < 0) [24,25,20,32,27] indicates strong electron-phonon interaction [34,35,36]. These results suggest that the CDW instability originates from momentum-dependent electron-phonon coupling.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is consistent with optical conductivity results in SrPt 2 As 2 [24] and the quasi-nesting features obtained by band structure calculations in SrPt 2 As 2 [26]. The negative curvature of the electrical resistivity temperature dependence (d 2 ρ/dT 2 < 0) [24,25,20,32,27] indicates strong electron-phonon interaction [34,35,36]. These results suggest that the CDW instability originates from momentum-dependent electron-phonon coupling.…”
Section: Discussionsupporting
confidence: 89%
“…The structure was first reported by Imre et al [23] to be a CaBe 2 Ge 2 -type structure at room temperature. In contrast, the XRD pattern reported by Imai et al [27] clearly demonstrated that SrPt 2 Sb 2 has not a tetragonal structure, but a lower symmetrical structure. However, the details of the structure in both phases and the magnetic properties near T = T 0 have yet to be identified.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…ThCr 2 Si 2 -type structure has been found in SrNi 2 As 2 , LaRu 2 P 2 , and SrPd 2 As 2 , etc. [6,7,10,11,15,17,23,24,29] [18,19]. Structural phase transition is found in BaNi 2 As 2 from a high-temperature tetragonal phase to a low-temperature triclinic phase at T = 130 K [30].…”
Section: Crystal Structurementioning
confidence: 99%
“…On the other hand, SC is also observed in other 122-type compounds formulated with AT 2 Pn 2 (A = alkaline-earth or rare-earth; T = transition metals; Pn = P, As or Sb) without iron [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. It has been reported that these 122-compounds show a variety of interesting phenomena, such as SC [1], heavy fermion [26], densed Kondo behavior [27], coexistence of SC and anti-ferromagnetism (AFM)/ferromagnetism (FM) /spin-density-wave (SDW) or charge density wave (CDW) [1,13,28].…”
Section: Introductionmentioning
confidence: 98%